Labour market inequality and the changing life cycle profile of male and female wages - Richard W. Blundell; Hugo Lopez; James P. Ziliak (Institute for Fiscal Studies (IFS), 2023)
We estimate the distribution of life cycle wages for cohorts of prime-age men and women in the US. A quantile selection model is used to consistently recover the full distribution of wages accounting for systematic differences in employment, permitting us to construct gender- and education-specific age-wage profiles, as well as measures of life cycle inequality within- and between-education groups and gender. Although common within-group time effects are shown to be a key driver of labor market inequalities, important additional differences by birth cohort emerge with older cohorts of higher educated men partly protected from the lower skill prices of the 1970s. The gender wage gap is found to increase sharply across the distribution in the first half of working life, coinciding with fertility cycles of women. After age 40, there has been substantial gender wage convergence in recent cohorts relative to those born prior to the 1950s.
Keywords: J3; J1; 330; Wage Inequality; Life Cycle Earnings; Employment; Quantile Selection; Gender Gaps